Evaluación integral de dos sistemas de producción de café en Veracruz, México - Escamilla Prado, E.=700 1 García Pérez, E.; Mosqueda Vásquez, R.; Santoyo Cortés, V.H.; Pacheco Velasco, J.E.
Sumario (Es)
Ilus.; 5 ref.
Keywords: COFFEA ARABICA; SISTEMAS DE CULTIVO; PRODUCCION; MEXICO; MEMORIA; SIMPOSIO